Genome-wide identification and analysis of the SnRK2 gene family in cowpea (Vigna unguiculata (L.) Walp.) reveals potential stress-responsive roles - Rajesh, S; Kavya, S; Navinraj, S; Radhamani, T; Anitha, T; Ramesh, S V (Plant Science Today, 2025)
Plants, owing to their sessile nature, have evolved mechanisms to adapt and overcome various abiotic stresses by activating different signaling pathways triggering accumulation of stress-associate proteins. A key regulator in Abscisic acid (ABA) signaling pathway, sucrose non-fermenting-1-related protein kinase 2 (SnRK2), is a plant-specific serine/threonine kinase family involved in osmotic stress responses. While members of this protein family have been analyzed in some plant species, their characterization in cowpea (Vigna unguiculata), a tropical food grain legume cultivated in Africa and Southeast Asia, remains unexplored. Drought stress significantly hampers the growth and productivity of cowpea, highlighting the need for functional studies of stress-related genes. The genes encoding SnRK2 in cowpea and their detailed characterization remain unexplored. The present study attempts to identify and characterize SnRK2 gene families in cowpea using bioinformatics tools. Analysis of the draft genome of Vigna unguiculata in NCBI and Phytozome databases revealed sixteen SnRK2 genes. In silico analysis were conducted to determine gene structure, transcript length and chromosomal mapping of the genes to Vigna unguiculata genome. Domain architectures of the SnRK2 proteins were predicted. Physico-chemical characterization revealed these proteins in sizes ranging 53 to 112 kDa with pI values of 4.99 to 9.59. All identified cowpea SnRK2 proteins are hydrophilic in nature. Analysis of the evolutionary relationship of SnRK2 with other related families showed three clusters based on the relatedness to Arabidopsis thaliana and thirteen other crops. Findings of this study provide valuable insights into cowpea SnRK2 gene family and its possible implications in plant stress tolerance.